E- GOVERNMENT DALAM PELAYANAN PENGADUAN MASYARAKAT PADA PROGRAM LAPOR PAK KAPOLRES Studi Kasus : Kepolisian Republik Indonesia Resor Karawang Pada Layanan Lapor Pak Kapolres: - Narayasa G, Moch Hexa; Azijah, Dewi Noor; Ramdani, Rachmat (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
E-Government is currently widely used in several state agencies to support the ease of providing services that can be accessed easily and from anywhere so that existing problems can be resolved immediately, its use in this study is at the Karawang Police as a means of public complaints which will later be directly received by a special team that handles the service, the use of E-Government reaps many benefits of course in service and makes it easier for the public to access information and provide complaints related to problems in their environment. The research method used is a qualitative method with a case study design where researchers will later see several phenomena or cases that have occurred in the field or social media as additional data. The results and discussion of several indicators have gone well, the support from various elements to implement the program certainly increases high confidence in the agency to respond quickly in overcoming a problem, supported by facilities and infrastructure and qualified human resources, of course the use of E-Government has many benefits felt by the people of Karawang Regency. The conclusion that researchers can provide is that the use and utilization of current technology must be carried out, this is of course to support the performance of an agency that requires working quickly and accurately in all conditions.